2016
DOI: 10.1055/s-0036-1584236
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deferoxamine on Fat Graft Survival

Abstract: The most important problem in fat transplantation is the unpredictable rates of resorption. Deferoxamine (DFO) is an iron-chelating agent with many useful functions including stimulating angiogenesis and antioxidant nature. The purpose of the study is to evaluate the effects of DFO on fat graft viability in rat model. A total of 24 Wistar rats were divided into three groups and 0.5 g of the left inguinal fat pad was extracted. In control group, fat grafts were implanted to the parascapular area without perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…Importantly, DFO was recently suggested to promote fat graft viability in a rat model. Temiz and colleagues described serial injections of 300 mg DFO into inguinal fat pads transplanted to parascapular subcutaneous pockets, which resulted in significantly greater weight measurements after two months (12). However, more inflammation and fibrosis was noted in DFO injected fat grafts, though no change in cellular apoptosis was appreciated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, DFO was recently suggested to promote fat graft viability in a rat model. Temiz and colleagues described serial injections of 300 mg DFO into inguinal fat pads transplanted to parascapular subcutaneous pockets, which resulted in significantly greater weight measurements after two months (12). However, more inflammation and fibrosis was noted in DFO injected fat grafts, though no change in cellular apoptosis was appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative, deferoxamine (DFO) has been studied as an angiogenic and antioxidant agent with the potential to improve fat graft survival (12). DFO, an FDA approved iron chelator for treating acute iron poisoning and chronic iron overload associated with frequent blood transfusions, has also been demonstrated to increase hypoxia-inducible factor -1 alpha (HIF-1α) activity and enhance expression of angiogenic growth factors (13, 14).…”
Section: Introductionmentioning
confidence: 99%
“…Well known as a treatment option for beta‐thalassemia and hemochromatosis, 64,65 iron chelating drugs have shown benefits in aesthetic medicine and plastic surgery. With their regenerative potential, they have the ability to increase the retention rate of fat grafts, the survival rate of free flaps, and the healing process of diabetic wounds 66,67 …”
Section: Discussionmentioning
confidence: 99%
“…72,73 Autologous fat grafts enriched with DFO have been shown to have increased graft survival and viability in rats. 74 A concern with intragraft injection of DFO, however, is that it may chelate and thus deplete iron, which can impair adipogenesis. 44,45,75 To circumvent this, preconditioning of irradiated recipient sites with DFO before fat grafting has been performed and we have found that this strategy improved vascularization before grafting, and ultimately enhanced volume of retained fat retained posttransplantation.…”
Section: Challenges Of Fat Grafting Into Irradiated Tissuementioning
confidence: 99%